Temporal Dynamics of the Default Mode Network Characterize Meditation-Induced Alterations in Consciousness - Panda, Rajanikant; Bharath, Rose D.; Upadhyay, Neeraj; Mangalore, Sandhya; Chennu, Srivas; Rao, Shobini L. (Frontiers in Human Neuroscience, 2016)
Current research suggests that human consciousness is associated with complex, synchronous interactions between multiple cortical networks. In particular, the default mode network (DMN) of the resting brain is thought to be altered by changes in consciousness, including the meditative state. However, it remains unclear how meditation alters the fast and ever-changing dynamics of brain activity within this network. Here, we addressed this question using simultaneous electroencephalography (EEG) and functional imaging (fMRI) to compare the spatial extents and temporal dynamics of the DMN during rest and meditation. Using fMRI, we identified key reductions in the posterior cingulate hub of the DMN, along with increases in right frontal and left temporal areas, in experienced meditators during rest and during meditation, in comparison to healthy controls. We employed the simultaneously recorded EEG data to identify the topographical microstate corresponding to the DMN. Analysis of the temporal dynamics of this microstate revealed that the average duration and frequency of occurrence of DMN microstate was higher in meditators compared to healthy controls. Both these temporal parameters increased during meditation, reflecting the state effect of meditation. In particular, we found that the alteration in the duration of the DMN microstate when meditators entered the meditative state correlated negatively with their years of meditation experience. This reflected a trait effect of meditation, highlighting its role in producing durable changes in temporal dynamics of the DMN. Taken together, these findings shed new light on short and long-term consequences of meditation practice on this key brain network.